Patterns of physical activity in 9 and 15 year-old children in Iceland - Nanna Ýr Arnardóttir 1982- (2008)
Physical activity is an important factor to prevent overweight and obesity, which is becoming more and more prevalent in both children and adults. Sedentary behaviour is a powerful predictor for many diseases and disorders. Physical activity declines with age, especially during adolescence. There are also differences between boys and girls, where girls are less physically active and their activity tends to be of lower intensity. Increased time in front of the television or computer during adolescence likely has an effect on this trend. The aim of this study was to examine the daily activity pattern of 9 and 15 year old (YO) children and explore the relationship between the activity pattern and body composition and fitness. A secondary aim was to explore how leisure- and screen time (TV, DVD, video and computer) is associated with different factors of the activity pattern. Participants in this study were 934 children born in 1988 and 1994, 9 and 15YO at that time. Measurements were taken from September 2003 to February 2004. The activity was assessed using an accelerometer which recorded the child´s activity for three to five days. Participants returning physical activity data which met the minimum criteria were 338 and 743 participants answered a questionnaire. The main findings were that the daily activity pattern varied considerably depending on both age and sex. 9YO children (girls= 528±166 kcounts/day (±SD), boys= 620±186 kcounts/day) were significantly more active than 15YO adolescents (girls= 425±130 kcounts/day, boys= 543±195 kcounts/day; F= 37.2; df= 1.334; p<0.001). Also, it was found that the activity pattern was not the same on weekends and weekdays (F= 27.4; df= 10.6;3535; p<0.001) and this difference depended on age (F= 12.6; df= 10.6;3535; p<0.001) and gender (F= 2.30; df= 10.6,3535; p= 0.009). Seven v independent components, were chosen which best described the nature and quality activity. These were calculated using Principal component analysis. Three of these components described ...